Thermal stability and epitope integrity of a lyophilized ricin toxin subunit vaccine. Issue 40 (25th September 2018) - Westfall, Jennifer; Yates, Jennifer L.; Van Slyke, Greta; Ehrbar, Dylan; Measey, Thomas; Straube, Richard; Donini, Oreola; Mantis, Nicholas J.
Abstract: Biodefense vaccine are destined to be stockpiled for periods of time and deployed in the event of a public health emergency. In this report, we compared the potency of liquid and lyophilized (thermostabilized) formulations of a candidate ricin toxin subunit vaccine, RiVax, adsorbed to aluminum salts adjuvant, over a 12-month period. The liquid and lyophilized formulations were stored at stressed (40 °C) and unstressed (4 °C) conditions and evaluated at 3, 6 and 12-month time points for potency in a mouse model of lethal dose ricin challenge. At the same time points, the vaccine formulations were interrogated in vitro by competition ELISA for conformational integrity using a panel of three monoclonal antibodies (mAbs), PB10, WECB2, and SyH7, directed against known immunodominant toxin-neutralizing epitopes on RiVax. We found that the liquid vaccine under stress conditions declined precipitously within the first three months, as evidenced by a reduction in in vivo potency and concomitant loss of mAb recognition in vitro . In contrast, the lyophilized RiVax vaccine retained in vivo potency and conformational integrity for up to one year at 4 °C and 40 °C. We discuss the utility of monitoring the integrity of one or more toxin-neutralizing epitopes on RiVax as a possible supplement to animal studies to assess vaccine potency.